Lidocaine for status epilepticus in adults. (3rd June 2015) - Zeiler, FA; Zeiler, KJ; Kazina, CJ; Teitelbaum, J; Gillman, LM; West, M
Abstract : Introduction: Our goal was to perform a systematic review of the literature on the use of intravenous lidocaine in adults for status epilepticus (SE) and refractory status epilepticus (RSE) to determine its impact on seizure control. Methods: All articles from MEDLINE, BIOSIS, EMBASE, Global Health, HealthStar, Scopus, Cochrane Library, the International Clinical Trials Registry Platform (inception to November 2014), and gray literature were searched. The strength of evidence was adjudicated using both the Oxford and GRADE methodology by two independent reviewers. Results: Overall, 13 studies were identified, with 11 manuscripts and 2 meeting abstracts. Seventy-six adult patients were treated for 82 episodes of SE/RSE. Patients had varying numbers of anti-epileptic drugs (AEDs), 1 to 12, on board prior to lidocaine therapy. During 69 of the 82 (84.1%) episodes of SE/RSE, phenytoin was on board. The dose regimen of lidocaine varied significantly. Overall, 70.7% of seizures responded to lidocaine, with complete cessation and greater than 50% reduction seen in 64.1% and 6.1% respectively. Patient outcomes were sparingly reported. Conclusions: There currently exists level 4, GRADE C evidence to support the consideration of lidocaine for SE and RSE in the adult population. Further prospective studies of lidocaine administration in this setting are warranted.